Efektivitas Inhalasi Aromaterapi Lemon Meredakan Gejala Emesis Gravidarum pada Ibu Hamil Trimester I di Puskesmas Jatiroto - Laeli Yatus Sulfa; Rani Safitri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Emesis gravidarum, which refers to feeling sick and throwing up during the early stages of pregnancy, women in the first - three months often go through it. Due to variation in hormone levels, especially an increase in hCG, estrogen, and progesterone, it can disrupt daily routines while lowering overall quality of life. As a non-pharmacological option, lemon aromatherapy is regarded as relatively safe; its limonene content is associated with a calming effect and may ease nausea by acting on the limbic system. The purpose of this research was to evaluate the efficacy of lemon essential oil treatment in the reduction of emesis gravidarum in first-trimester women who are pregnant in the catchment area of the Jatiroto Health Center. Twenty participants chosen using targeted sampling participated in a pre experimental, single-group, pretest - posttest research. Participants inhaled lemon aromatherapy over a period of 5-7 days, with an observation sheet used to record conditions both before and following the treatment. Wilcoxon rank-sum analysis (α = 0.05) was employed in the data analysis process. The findings indicated that  symptom severity, initially dominated by moderate and severe categories, shifted toward the mild category following the intervention, with the difference reaching statistical significance p equals 0.000. Hence one may deduce that aromatherapy with lemon in the first trimester helps to relieve morning sickness in expectant women.